Supporting school ICT uptake: The ASK School ICT Competence Management System - Sergis, S.; Sholla, I.; Zervas, P.; Sampson, Demetrios (Institute of Electrical and Electronics Engineers Inc., 2015)
© 2014 IEEE. In all European countries, initiatives are implemented towards promoting the use of Information and Communication Technologies (ICT) in schools. However, the current level of school ICT uptake remains low, due to the interrelation of a wide range of factors, including teachers' ICT competences and strategic school Leadership planning. In this context, there is a need for systems that will facilitate schools in capturing the contribution of these factors and meaningfully process the data for informed strategic planning. The aim of this paper is to present a web-based system, namely the ASK School ICT Competence Management System, which takes a step towards the aforementioned needs for effective school ICT uptake monitoring and management.